Uso de equações diferenciais ordinárias na modelagem matemática - TEIXEIRA, Josiel Monteiro (2024)
The word model can have different meanings depending on the area of knowledge to which it is applied. It can be something related to form, method, arrangement or even manner. From this perspective, the aim is for models to be able to simplify reality, so that individuals can understand how it works in a general sense, being a part of that reality. This requires the use of experimental structures and even mental concepts. If the reality you want to represent is very complex, it can be subdivided into several others, and a model is generated for each one. Thus, the aim of a model is to build it in such a way that it can understand reality in the simplest way and, at the same time, be as complete and accurate as possible. Among the various types of models, there are those that use mathematics and are therefore called mathematical models. Mathematical models seek to represent reality by means of equations. However, solving equations is not always easy to understand, even when they are used to represent a single phenomenon. Even so, mathematics is a great ally in this process of representation. The aim of this research is to understand how a mathematical model works in conjunction with first- and second-order differential equations, with a practical application to situations in society. The methodology used in the research was qualitative, aiming to understand the social aspects in line with the concept of mathematical models in the study of differential equations. Data was collected by means of bibliographical research in teaching materials, gathering concrete information on the subject studied.